Civilising subject(s): drawing pedagogy in Bombay in the age of industrial capitalism and empire. - Mulgund, Deepti (Paedagogica Historica, 2025)
This article charts a critical history of drawing, as it was taught within "general" schooling in colonial Bombay (now Mumbai), beyond the artisanal workshop, art, and industrial schools. Rather than children's creative or subjective expression as it is commonly seen today, drawing's presence in the school curriculum was a sign of the efforts being taken to create a workforce suitable for industrial capitalism, in Britain and in India. Analysing archival sources, and situating them within the broader discourses around colonialism, work, and the industrial subject, the article points out that when drawing was taught in Bombay it was hamstrung by issues metropolitan in origin, viz. course design, inconsistent pedagogic vision, lack of financial outlay as well as local conditions of low industrialisation. Similar problems plagued drawing in Britain. However, colonial power relations held Indian teachers and school-goers responsible for drawing's "failures" in addressing the crisis of technical skilling and employment generation in India, while in Britain the critique was directed towards the system. Drawing – despite these "failures" – came to be valued as a practice necessary in and of itself. Drawing, the article contends, offered an embodied and verifiable response to wage labour, as seen in its unfolding in the colony, i.e. a moral technology geared towards wage labour.